Dissociating Contingency Awareness and Conditioned Attitudes: Evidence of Contingency-Unaware Evaluative Conditioning - Hutter, Mandy; Sweldens, Steven; Stahl, Christoph; Unkelbach, Christian; Klauer, Karl Christoph (Journal of experimental psychology. General, 2012)
Whether human evaluative conditioning can occur without contingency awareness has been the subject of an intense and ongoing debate for decades, troubled by a wide array of methodological difficulties. Following recent methodological innovations, the available evidence currently points to the conclusion that evaluative conditioning effects do not occur without contingency awareness. In a simulation, we demonstrate, however, that these innovations are strongly biased toward the conclusion that evaluative conditioning requires contingency awareness, confounding the measurement of contingency memory with conditioned attitudes. We adopt a process-dissociation procedure to separate the memory and attitude components. In 4 studies, the attitude parameter is validated using existing attitudes and applied to probe for contingency-unaware evaluative conditioning. A fifth experiment incorporates a time-delay manipulation confirming the dissociability of the attitude and memory components. The results indicate that evaluative conditioning can produce attitudes without conscious awareness of the contingencies. Implications for theories of evaluative conditioning and associative learning are discussed. (Contains 3 tables, 6 figures and 10 footnotes.)